2017
DOI: 10.1159/000477967
|View full text |Cite
|
Sign up to set email alerts
|

Potential Gender-Related Aging Processes Occur Earlier and Faster in the Vermis of Patients with Bipolar Disorder: An MRI Study

Abstract: Background: In the last decades, there has been increasing interest in investigating the role of the vermis in bipolar disorder (BD), especially because of its involvement in cognitive processes. The main aims of this study were to explore the integrity of the vermis and elucidate the role of demographic and clinical variables on vermis volumes in BD patients, stratified according to gender. Methods: T1-weighted images were obtained for 38 BD patients and 38 healthy controls using a 1.5-T MRI scanner. Images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Along with age, gender might play a role in the neurobiology of BD as the disease have gender-related clinical differences in terms of clinical onset, presentations, prevalence of mood states and treatment responses (Arnold, 2003). Interestingly, imaging research in BD also reported that gender may play a key role in influencing brain structural and functional deficits within prefrontal and limbic areas (Jogia et al, 2012) as well as in vermis volumes (Serati et al, 2017). However, the majority of the studies took these effects into consideration by adding them as covariates in the statistical analysis of imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…Along with age, gender might play a role in the neurobiology of BD as the disease have gender-related clinical differences in terms of clinical onset, presentations, prevalence of mood states and treatment responses (Arnold, 2003). Interestingly, imaging research in BD also reported that gender may play a key role in influencing brain structural and functional deficits within prefrontal and limbic areas (Jogia et al, 2012) as well as in vermis volumes (Serati et al, 2017). However, the majority of the studies took these effects into consideration by adding them as covariates in the statistical analysis of imaging data.…”
Section: Discussionmentioning
confidence: 99%